2004
DOI: 10.1111/j.1365-294x.2004.02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by distance and post‐glacial range expansion in the rough‐skinned newt, Taricha granulosa

Abstract: Allozymes and mitochondrial DNA sequences were used to examine the phylogeographical history of the rough-skinned newt, Taricha granulosa, in western North America. Nineteen populations were analysed for allozyme variation at 45 loci, and 23 populations were analysed for cytochrome b sequence variation. Both data sets agree that populations in the southern part of the range are characterized by isolation by distance, whereas northern populations fit the expectations of a recent range expansion. However, the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 73 publications
2
89
0
Order By: Relevance
“…Taking no account of anthropogenic influence, isolation by distance or/and geography might play important role(s) in the evolutionary history of amphibians and reptiles with limited vagility (e.g., Kuchta and Tan, 2005). In the present study, isolation-by-distance appears to be a factor involved in the population genetic structuring of D. acutus.…”
Section: Isolations and West-east Divisionmentioning
confidence: 62%
“…Taking no account of anthropogenic influence, isolation by distance or/and geography might play important role(s) in the evolutionary history of amphibians and reptiles with limited vagility (e.g., Kuchta and Tan, 2005). In the present study, isolation-by-distance appears to be a factor involved in the population genetic structuring of D. acutus.…”
Section: Isolations and West-east Divisionmentioning
confidence: 62%
“…Studies of multiple taxa within the region have shown evidence of phylogeographic structure (e.g., refs. [33][34][35]. Moreover, multiple studies have shown higher levels of phylogeographic differentiation in California than in the Pacific Northwest, where populations of many species became established only after the retreat of Pleistocene glaciers (26,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Our phylogenetic placement of Notophthalmus and Taricha is congruent with the allozymebased phylogeny of Hayashi and Matsui (1989). Relationships among species within Notophthalmus and Taricha have not previously been explored, although a number of studies have addressed phylogeography within individual species (Gabor and Nice, 2004;Kuchta and Tan, 2005;Reilly, 1990;Tan and Wake, 1995). Within Notophthalmus, Bayesian analysis strongly groups N. perstriatus and N. viridescens as sister species (Fig.…”
Section: Phylogenetics Of Notophthalmus and Tarichamentioning
confidence: 99%